Analisis Perbedaan Volume Lalu Lintas Sepeda Motor pada Pagi dan Sore sebagai Indikator Kinerja Luas Jalan Berdasarkan PKJI 2014 - Azam Ibnu Sabil; Amri Gunasti (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
This study aims to analyze the differences in motorcycle traffic flow (Q) during the morning and afternoon peak hours as an indicator of roadway operational performance, referring to the Indonesian Road Capacity Guidelines (PKJI) 2014, with a case study on Mawar Street–Wijaya Kusuma Street, Jember Regency. The research data were obtained from 12 observation points through traffic surveys that recorded motorcycle traffic flow in vehicles per hour (veh/h). The analytical methods used include descriptive statistical analysis, normality testing, and paired sample t-test. The results show that the average motorcycle traffic flow during the morning peak hour is 115.58 veh/h with a standard deviation of 62.97, while during the afternoon peak hour it is 63.25 veh/h with a standard deviation of 28.57. The paired sample t-test yields a significance value of 0.015 (p < 0.05), indicating a statistically significant difference between morning and afternoon traffic flows. These findings suggest that the level of roadway capacity utilization is higher during the morning peak hour, which is closely associated with dominant routine travel activities such as commuting to work and school. The results of this study are expected to serve as a basis for evaluating roadway operational performance and to support traffic management and traffic engineering planning aimed at improving road network performance and reducing congestion.